The Effect of Profitability and Leverage on Tax Avoidance (Empirical Studies on Chemical and Basic Industrial Companies listed on the IDX) - Masta Sembiring (Journal of International Conference Proceedings (JICP), 2022)
The study aims to determine “The Effect of Probability and Leverage on Tax Avoidance (Empirical Study on Basic and Chemical Industry Companies Listed on the IDX)”. The type of research used is quantitative research. Population in this study, 19 basic and chemical industrial companies were listed on the Indonesian stock exchange in 2016 – 2020. The method used in this study to determine the sample is purposive sampling with as many as 9 companies for 5 consecutives years. The data collection used is the documentation method by retrieving financial statement data on the Indonesian stock exchange. The data that is ready to be processed will then be tested using the SPSS version 21.0 program. The data analysis methods used in this research are descriptive statistics, multiple linear regression, classical assumption test and hypothesis testing. The results of this study show that probability has no significant effect on tax avoidance, this can be proven by the significance value of 0.672 > 0.05, and conversely leverage has a significant effect tax avoidance with a significant value of0.021 < 0.05 and simultaneously probability and leverage have no significant effect on tax avoidance with evidence of 0.061 > 0.05. Keywords: Profitability, Leverage and Tax Avoidance